Synthesis of unsymmetrical NCN′ and PCN pincer palladacycles and their catalytic evaluation compared with a related SCN pincer palladacycle12. Issue 8 (15th June 2016) - Roffe, Gavin W.; Tizzard, Graham J.; Coles, Simon J.; Cox, Hazel; Spencer, John
Abstract : A series of unsymmetrical palladacycles have been synthesised and evaluated as catalysts in aldol and vinyl epoxide coupling chemistry. Abstract : 1-(3-(Pyridin-2-yl)phenyl)methanamine derivatives have been synthesized and underwent C–H bond activation to afford unsymmetrical NCN′ pincer palladacycles, which were characterised in the solid state. 2-Pyridinyl-phenol and -benzyl alcohols were then used as precursors to unsymmetrical PCN pincer palladacycles. Catalytic applications, where the palladacycle remains in the Pd(ii ) state, have been carried out and show good activity and selectivity.